(untitled) ("Temas Sociais" Journal, 2023)
The study analyses the conditions of access and allocation of student residence support made possible by the interviews conducted by social workers at public universities, namely at four Portuguese public universities. It also sought to identify the residents’ representation of the conditions of access to and allocation of social action support in Portuguese higher education and to analyze the role of social workers in ensuring this access and the allocation of a place in the student residence. The study is qualitative and qualitative by nature. Evidence gathered from institutional reports and the current national legislation is presented, as well as from an inquiry applied to the residents. The results assemble the aims defined to students’ housing with the student’s representation of the access conditions and support attribution, demonstrating that the Students’ Services produce effects on said representations. Besides, the results point out the effects of the interview, especially on the Services that do more frequently this procedure. So Social Work justifies its action using an instrument that historically underlies the social diagnosis, promoting access to housing and social and pedagogical orientation.